GRAFT COPOLYMERIZATION OF ACRYLAMIDE ONTO STRAW CELLULOSE: EFFECT OF COMPOSITION OF REACTANTS ON REACTION PERFORMANCE - Hoang Thi, Phương (Journal of Military Science and Technology, 2021)
The effect of cellulose fiber size, acrylamide (AM) concentration, monomer/fiber ratio and initiator concentration in the polymer graft polymerization process on cellulose obtained from straw was researched. The material was characterized by FTIR spectra, thermal gravimetric analysis (TGA) and their morphology were investigated by SEM images. The results show that the grafted product has a higher thermal stability compared to the grafted yarn. SEM image is evidence that acrylic grafting took place on cellulose fiber with grafting yield (%GY) = 35,2%, grafting efficiency (%GE) = 29,4% and total conversion percentage (%TC) = 89,9%. Therefore, the fiber size is 0.2 cm, acrylamide with concentration = 1.5 M, monomer/fiber ratio = 2.5 g/g and initiator concentration = 0.083 M was chosen for the process of grafting acrylamide to cellulose obtained from straw.